Выполните умножение: 1)a^3b/15c*(-3c/a^2b^2)
2)18y^3*4x^2/9y^5
3)a^3^nb^n+4/c^n+3*c^2^n+3/a^2^nb^n+1


Выполните умножение: 1)a^3b/15c*(-3c/a^2b^2)2)18y^3*4x^2/9y^53)a^3^nb^n+4/c^n+3*c^2^n+3/a^2^nb^n+1

b00777 b00777    3   21.01.2022 20:09    0

Ответы
aizada14 aizada14  21.01.2022 20:10

1) (2a^2 - 3b) * (a^2 + 2ab + 5b^2) = 2a^4 + 4a^3 * b + 10a^2 * b^2 - 3a^2 * b - 6ab^2 - 15b^3;

2) (x^2 - 2xy) * (x^2 - 5xy + 3y^2) = x^4 - 5x^3 * y + 3x^2 * y^2 - 2x^3 * y + 10x^2 * y^2 - 6xy^3 = x^4 - 7x^3 * y + 13x^2 * y^2 - 6xy^3;

3) (x - y) * (x^3 + x^2 * y + x * y^2 + y^3) = x^4 + x^3 * y + x^2 * y^2 + xy^3 - x^3 * y - x^2 * y^2 - xy^3 - y^4 = x^4 - y^4;

4) (a + b) * (a^3 - a^2 * b + a * b^2 - b^3) = a^4 - a^3 * b + a^2 * b^2 - ab^3 + a^3 * b - a^2 * b^2 + ab^3 - b^4 = a^4 - b^4;

5) (5a - 4b) * (a^3 + 2a^2 * b - 5a * b^2 - 3b^3) = 5a^4 + 10a^3 * b - 25a^2 * b^2 - 15ab^3 - 4a^3 * b - 8a^2 * b^2 + 20ab^3 + 12b^4 = 5a^4 + 6a^3 * b - 33a^2 * b^2 + 5ab^3 + 12b^4;

6) (2x + 3y) * (x^3 + 3x^2 * y - 3x * y^2 + 4y^3) = 2x^4 + 6x^3 * y - 6x^2 * y^2 + 8xy^3 + 3x^3 * y + 9x^2 * y^2 - 9xy^3 + 12y^4 = 2x^4 + 9x^3 * y + 3x^2 * y^2 - xy^3 + 12y^4.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика